Využití bioplynu ve spojení s kogenerací - Fojtík, Martin (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií)
Bakalářská práce je zaměřena na řešení aktuální problematiky využívání biologických odpadů s použitím kogenerace. Úkolem je navrhnout a zhodnotit provoz kogeneračního systému spolupracujícího s bioplynovou stanicí. První část je věnována vzniku bioplynu a biomase vhodné pro výrobu bioplynu a dále také bioplynové technologii. Principem kogenerace a komparací jednotlivých primárních jednotek se zabývá část druhá. V závěrečné části je zhodnocen provoz bioplynové kogenerace.

This bachelor’s thesis is specialized on the solution of actual problems dealing with the exploitation of biological wastes usány combined heat and power. The task is to suggest and valorize the running of combined heat and power system cooperating with a bio-gas station. The first part is devoted to the rise of biogas and biomass which is fit for the production of biogas, further also to the biogas technology. The second part of of this work deals with the principle of combined heat and power, as well as with the comparation of single prime units. The running of biogas combined heat and power is reviewed in the final part.
Utilization biogas for combined heat and power
Keywords: bioplyn; kogenerace; alternativní zdroj; biogas; combined heat and power; Non-conventional energy sources